Subsistence Agriculture and Food Sustainability in East Alego Location, Siaya County, Kenya - Oduor, Teresa Atieno (JOOUST, 2020)
Food sustainability in East Alego location has faced many challenges. Even though the area is endowed with natural conditions favorable for subsistence agriculture but, most households still experience food unsustainability. The main objective of the study was to determine, the effects of subsistence agriculture on food sustainability. The specific objectives were; to establish how subsistence agriculture affects food sustainability, to evaluate the effects of farm produce sales and finally to assess the coping strategies during food shortage periods. Descriptive research design was used together with research instruments such as observations, interview schedules and administration of questionnaires. The study adopted stratified sampling technique and simple random sampling design with a sample size of 327 households out of 2381 targeted farm households in the study area. Data from the field was analyzed using measures of central tendencies such as mean, mode and median. Frequencies and percentages were also used to present data using tables, pie charts, bar graphs, line graphs and photographs. Tests such as Mann Whitney U-Test, Kruskal-Wallis Test, Spearman`s rank order and Chi- square statistics were used in analyzing data from the field. A Kruskall-Wallis Test revealed that there was a significant effect on mono – cropping of maize in East Alego location; Where (H = 8.07, p ˂ .05). From the mean ranks Umala Sub-location had a higher mean maize production (10) than Olwa (9.25) and Ulafu (9.25) Sub-locations. Tabulated (critical) 𝑋 value was 225.231 which was greater than the tabulated (critical) 𝑋2 value at 0.05 was 11.070 while calculated 𝑋2 value (11.070). Therefore, it was concluded that dependence on rain fed agriculture was significantly affecting crop production in East Alego location. A spearman’s rank correlation value (r) = 0.9 was closer to 1 and signified a strong/high positive correlation on the benefits of livestock production to farmers. A Mann Whitney U-Test value of 31 was calculated and it was above the mean and median values of 8.5 respectively and almost twice the number of the observations made (16) showing more significant effect on food sustainability in Umala/Ulafu Sub-locations than in Olwa Sub-location. The study revealed that majority of subsistence farmers of East Alego location were not embracing modern agricultural practices that could lead to diversity in crop and animal production. This could lead to unsustainable food because of lack of maximized integration of crop and livestock, together with sales of the little farm produce could lead to food unsustainability. Nearly 81% of the respondents suggested keeping of mixed animals for their produce and use of dung/farmyard manure as farm input to improve soil fertility so that crop production could be improved for food sustainability. Additionally, respondents (53%) suggested diversification of income in order to reduce the vulnerability of the households during food shortage periods. Subsistence farmers of East Alego location should be encouraged to embrace modern agricultural technology for food sustainability.